A Phosphorous History: William Carlos Williams’ In the American Grain - Antonia Rigaud (European Journal of American Studies)
Through a reading of William Carlos Williams’ In the American Grain (1925), this paper seeks to look at the questions raised by the writing of history in the modernist context and to explore Williams’ particular definition of history.Williams’ historical project turns history into a literary question through a text that is a collage of very different voices, narratives, and shifts of perspective, thus raising the question of how to write history. Williams’ foreword suggests the impossibility of writing a true history and points rather to the desire to capture an evanescent reality, what he calls “the phosphorus of the life”. Williams attempts to write the history of a “homemade world” to use Hugh Kenner’s eloquent phrase; rather than looking at Europe as his friend Pound was doing at the time, the text presents variations on recurring motifs of American history, problematizing the notion of a “new” continent and of the discovery of place. Williams’ poetic repossession of history calls for a reflection on the type of history he sought to write. In the American Grain looks at the “beginners” that have made American history, from the Spanish explorers to Poe, and questions the naïve notion of “beginning”. William Carlos Williams’ In the American Grain is a biography of the American cultural imagination that puts in dialogue the national epic with a perspectival counter history.